Abnormal expression of homeobox c6 in the atherosclerotic aorta and its effect on proliferation and migration of rat vascular smooth muscle cells. (12th August 2020) - Long, Xiangshu; You, Ganhua; Wu, Qiang; Zhou, Yu; Yu, Fuxun; Xiao, Yan; Deng, Shiyan; Song, Fang; Huang, Jing; Tian, Maobo
Abstract: Homeobox c6 (Hoxc6) affects the proliferation, migration, and infiltration of malignant tumor cells; however, the effect of Hoxc6 on atherosclerosis (AS) as well as the proliferation and migration of vascular smooth muscle cells (VSMCs), which play a role in promoting AS, has not yet been well clarified. In the present study, we tested the hypothesis that Hoxc6 affects the proliferation and migration of rat VSMCs, and hence is involved in AS. The results showed that the expression of Hoxc6 mRNA and protein was higher in normal rat aortic wall than in the myocardium. Subsequently, a rat model of AS was established by high-fat feeding for 2 months. The expression of Hoxc6 mRNA and protein was increased significantly in AS lesions, while the expression of p53 protein was decreased and that of proliferating cell nuclear antigen (PCNA) was increased. Moreover, not only the proliferation and mobility of cells in normal culture were decreased, but also the proliferation was stimulated by oxidized low-density lipoprotein, which was decreased after downregulation of Hoxc6 expression in VSMCs in rat. Consecutively, the expression of PCNA protein was decreased, while that of p53 was increased. These results indicated that Hoxc6 is probably involved in AS via p53 and PCNA by affecting the proliferation and migration of VSMCs.